Influence of Timing of Postoperative Weight-Bearing on Implant Failure Rate Among Older Patients With Intertrochanteric Hip Fractures: A Propensity Score Matching Cohort Study - Jia, Xiaoyang; Qiang, Minfei; Zhang, Kun; Han, Qinghui; Wu, Ying; Chen, Yanxi (Frontiers in Medicine, 2021)
Introduction: The purpose of this study was to determine whether immediate weight-bearing as tolerated increased the risk of implant failure and decreased functional outcomes compared with restricted weight-bearing. Methods: From January 2010 to December 2018, 1,125 consecutive patients (≥65 years) with intertrochanteric fractures were identified. Of them, 130 patients were excluded, resulting in 995 patients in final cohort (563 receiving immediate weight-bearing and 432 receiving restricted weight-bearing). Propensity score (PS) matching yielded 403 patient pairs. Primary outcome was implant failure at 12 months. Secondary outcomes were implant failure at 3 months, functional outcomes at 12 months, and time to full weight-bearing. Results: Among 806 patients who were matched by PS, the mean age was 77.8 years (SD, 7.6), and 603 patients (74.8%) were women. After matching, there was no significant difference between immediate (10.0% [39/389]) and restricted (9.1%, [35/385]) weight-bearing for implant failure at 12 months (absolute risk difference, 0.93% [95% CI, −3.26 to 5.13%]; RR, 1.11 [95% CI, 0.69 to 1.80]; p = 0.66). Additionally, no significant difference was seen for implant failure at 3 months and functional outcomes at 12 months. Patients with immediate weight-bearing had shorter time to full weight-bearing (mean [SD], 87.6 days [7.5] vs. 121.3 days [11.0]; mean difference, −33.7 [95% CI, −35.0 to −32.3]; p < 0.001). Conclusions: Among older patients with intertrochanteric fractures, receipt of immediate weight-bearing as tolerated did not increase risks of implant failure or worsen functional outcomes compared with receipt of restricted weight-bearing. However, patients receiving immediate weight-bearing had a shorter time to full weight-bearing.